Caracterization of stripline discontinuities using a variational technique - Brito, Freddy (Rev. Téc. Fac. Ing. Univ. Zulia)
The model of rectangular waveguide with magnetic walls, is employed to calculate a basis function that allows the development of the electromagnetic field at both sides of the discontinuity produced by a simetrical variation in the width of the central conductor of the stripline. Applying the continuity conditions, and taking as a basis the corresponding function for the least width line, we obtain a variational expression that allows the deduction of the elements of the transmission matrix in current and voltage, therefore the dispersion matrix ([S]). The proposed method arrives directly to the equivalent circuit of the discontinuity, and lends itself confortably to the use of computation tools in calculating the matrix [S] for N symetrical discontinuities in cascade. This way, one can design such structures as filters and impedance transformers, and study their frequency response. The results obtained show an excellent agreement with those published in the literature, indicating this way the exactness and relevance of the method proposed in this work.